Crime and media - Jewkes, Yvonne, 1966-; Sage eBooks (London : SAGE, 2009)
The relationship between the media and crime is a topic of extremely lively debate and research internationally. With Yvonne Jewkes' background in both media studies and criminology she introduces readers to the most salient themes and puts together the definitive collection on the topic.
v. 1. Theorizing crime and media -- v. 2. Media representations of crime and criminal justice -- v. 3. Emerging/new media and crime.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Mass media and crime; Electronic books